1993
DOI: 10.3109/08941939309141190
|View full text |Cite
|
Sign up to set email alerts
|

Healing after Arterial Dilatation with Radiofrequency Thermal and Nonthermal Balloon Angioplasty Systems

Abstract: Thermal balloon angioplasty has been proposed as a means of reducing acute and delayed reclosure of arteries after percutaneous transluminal balloon angioplasty. A radiofrequency (rf) balloon catheter was used to perform thermal balloon angioplasty on canine arteries in vivo. The histologic appearance of rf-treated sites was compared with that of control sites treated by conventional percutaneous transluminal angioplasty. Acutely, rf-treated sites showed a reduced medial cellularity with preservation of intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The time course of bone regeneration in our study was markedly slowed in comparison with previous studies, supporting recent findings that heat-injured bone maintains only an inferior capacity to regenerate [16,28]. Recent studies have shown that revascularization begins one to 2 weeks after radiofrequency thermal balloon angioplasty, but is not complete until 4 weeks following treatment [29]. Thus, the delayed progress of bone regeneration in our study may result from thermal injury not only to bone but also to vascular structures, depriving subchondral tissue of the blood supply required for rapid growth.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The time course of bone regeneration in our study was markedly slowed in comparison with previous studies, supporting recent findings that heat-injured bone maintains only an inferior capacity to regenerate [16,28]. Recent studies have shown that revascularization begins one to 2 weeks after radiofrequency thermal balloon angioplasty, but is not complete until 4 weeks following treatment [29]. Thus, the delayed progress of bone regeneration in our study may result from thermal injury not only to bone but also to vascular structures, depriving subchondral tissue of the blood supply required for rapid growth.…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies have shown that revascularization begins one to 2 weeks after radiofrequency thermal balloon angioplasty, but is not complete until 4 weeks following treatment [29]. Thus, the delayed progress of bone regeneration in our study may result from thermal injury not only to bone but also to vascular structures, depriving subchondral tissue of the blood supply required for rapid growth.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, the distribution and extent of the proliferative response after RF thermal balloon angioplasty have been shown to be less than those seen after nonthermal balloon angioplasty. Thermal sites are considerably less prone to the development of myointimal hyperplasia, which may have beneficial effects on arterial healing after angioplasty [18].…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of IH can be achieved by reduction of the number of proliferating SMCs in the vessel wall. Thermal methods, photodynamic therapy, external irradiation and brachytherapy have been used (55, 62, 96, 103, 114–116, 143, 178, 186, 202, 215). Radioactive stents were also constructed (179, 217).…”
Section: Prevention Of Ihmentioning
confidence: 99%